Impact of educational intervention for improving Malaysian parents’ knowledge towards their children immunization - Awadh, Ammar Ihsan JawaD; Hassali, Mohamed Azmi; Al-lela, Omer Qutaiba; Bux, Siti Halimah; Elkalmi, Ramadan Mohamed Mahmod; Ab. Hadi, Hazrina (2014)
Background: Parents are the primary health decision-maker for their children. This fact makes parents’ knowledge regarding immunization in general has great impact on their children immunization status. Aims: To assess the knowledge of parents in Malaysia towards their children immunization and to evaluate the effectiveness of an educational seminar for improving parents’ knowledge towards their children immunization. Methods: A cross-sectional study using pre- and post- intervention design was conducted with a sample of 73parents. Changes in knowledge scores before and after the educational seminar were measured. Both descriptive and inferential statistics were used whenever appropriate. Frequencies and percentages were used to describe the respondents’ demographic information. Wilcoxon Signed ranks test and The McNemar χ2 test were applied to compare the differences in knowledge before and after the seminar whenever appropriate. Results: Seventy three parents agreed to participate in this educational seminar, majority of them were mothers (n= 64; 87.7%). A comparison of parents’ knowledge before and immediately after the implementation of the educational seminar showed significant differences. The mean ± standard deviation (SD) of the Knowledge scores of immunization significantly increased compared to the baseline following the intervention 12.60±2.69 to 16.03±1.87 (p<0.001), the possible score in knowledge domain ranged from zero to 20. Conclusion: Parents’ knowledge towards immunization improved significantly after the educational intervention. Therefore, introducing educational programs for parents to improve their knowledge about immunization is needed.